Cord compression secondary to intradural ossification. - Lawson-Smith, M; Green, A; Teddy, P (2006)
The authors describe two patients presenting with a previous history of spinal trauma and a several-year history of sensory changes secondary to spinal cord compression. Both patients underwent laminectomy and spinal decompression operations. In both cases intradural bone causing neural compression was removed at operation. Potential mechanisms to explain intradural ossification and the relevant literature are reviewed.